ANALISIS SENTIMEN TERHADAP PROGRAM MERDEKA BELAJAR – KAMPUS MERDEKA PADA TWITTER MENGGUNAKAN SUPPORT VECTOR MACHINE - Ni'ma Kholila (Antivirus : Jurnal Ilmiah Teknik Informatika, 2021)
Merdeka Belajar - Kampus Merdeka Program as one of the public policies by the Ministry of Education, Culture, Research, and Technology, cannot be separated from public opinion. Opinions are divided into three categories, positive opinions, negative opinions, and neutral opinions. The public expresses opinions through various social media platforms. As a simple social media, Twitter actually has an influence on the process of forming and directing public opinion. Tweet data with the keyword Merdeka Belajar - Kampus Merdeka between August 2020 and February 2021, is used to conduct sentiment analysis to identify the direction of public opinion towards Merdeka Belajar - Kampus Merdeka Program. Sentiment analysis using Support Vector Machine can be applied to predict the direction of a person's sentiment towards the Program Merdeka Belajar – Kampus Merdeka, both positive and negative sentiments. Based on the test results, it can be concluded that the F-measure accuracy value for the positive class is 94.8% and the F-measure accuracy value for the negative class is 95%.